THE ISSUE OF ECONOMIC CRISES AND CYCLICAL FLUCTUATIONS IN POLISH ECONOMIC THOUGHT IN THE INTERWAR PERIOD - Bochenek, Mirosław (Ekonomia i Prawo. Economics and Law, 2016)
This paper presents the considerations of Polish economists about the economic crises and the business cycle in the interwar period. According to E. Taylor, the causes of the then crisis of overproduction, accompanied by the phenomenon of price scissors, included varied elasticity of demand for agricultural products and industrial products, as well as monetary inflation and new technical inventions. E. Lipiński believed that the crisis was a result of overinvestment. State interventionism in the economies did not ease, but aggravated the crisis on a global scale. W.M. Zawadzki pointed to the nature of the crisis in Poland as being due to economic underdevelopment, low consumption, and a huge shortage of capital. J.W. Libicki took the view that an analysis of the crisis in agriculture should be combined with an analysis of profitability of agricultural production. A. Krzyżanowski linked production fluctuations with changes in investment demand, and the latter with the assessment of profitability, which depends on the interest rate. A. Heydel explained the business cycle with an incorrect interest rate policy. At the same time, he postulated that the state should refrain from interference in economic life. On the other hand, M. Kalecki pointed to the excessive optimism of businesses, causing an increase in investment, which leads to changes in global demand, as a cause of fluctuations. He advocated the inflationary financing of public works by the state.